Red and White Meat Intake in Relation to Mental Disorders in Iranian Adults - Kazemi, Shiva; Keshteli, Ammar Hassanzadeh; Saneei, Parvane; Afshar, Hamid; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2021)
Background: The association between meat consumption and mental disorders is less investigated in Iranian population. We examined the association between meat consumption and prevalence of symptoms of depression, anxiety and psychological distress in Iranian adults. Methods: This cross-sectional study included 3362 participants aged 18-55 years old. A dish-based 106-item semi-quantitative food frequency questionnaire (FFQ) was used to assess usual dietary intake of study population. Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), all validated in Iranian population, were applied to collect data on symptoms of anxiety, depression and psychological distress, respectively. Results: The prevalence of symptoms of depression, anxiety and psychological distress in the study population was 28.6, 13.6 and 22.6%, respectively. After considering potential confounders, individuals in the top quartile of red meat intake had 43% increased risk of depression symptoms (OR=1.43; 95%CI: 1.09-1.89), compared to those in the first quartile. No significant relation was observed between red meat intake and anxiety or psychological distress symptoms. White meat consumption was not associated with mental disorders. Stratified analysis by sex showed that male participants in the highest quartile of red meat intake had 92% greater risk of depression symptoms (95%CI: 1.17-3.15) than those individuals in the lowest category. Red and white meat intake was not associated with mental disorders in women. In overweight or obese individuals, despite lack of any association between red meat intake and mental disorders, high intake of white meat was associated with a lower odds of psychological distress symptoms (OR=0.64; 95%CI: 0.42-0.99) and a lower risk of depression symptoms (OR= 0.68; 95%CI: 0.45-1.00). In normal weight participants, those in the highest quartile of red meat intake had greater odds for depression symptoms than those in the lowest quartile (OR= 1.66; 95%CI: 1.14-2.42). Conclusions: We found that red meat consumption was associated with increased risk of depression symptoms, especially in men and normal weight participants. In overweight or obese participants, white meat intake was inversely associated with psychological distress symptoms.